The Effect of the Propeller Cards Strategy in Mental Focus of Intermediate Students Science for First-Year (Journal of the College of Basic Education, 2024)
The research aims to determine the effect of the propeller card strategy on the mental focus of first-year intermediate science students. To achieve the goal of the research, the following null hypothesis was developed: There is no statistically significant difference at the level of significance (0.05) between the average scores of the students of the experimental group who are taught according to the steps of the propeller card strategy and the average scores of the students of the control group who are taught according to the usual method of mental focus. To test the validity of the null hypothesis, the researcher applied his experiment and chose the design for it. A quasi-experimental study with partial control for the experimental and control groups with a dimensional measure of mental focus. The research sample was intentionally selected from the first-grade intermediate students of Salim Al-Basri Middle School for Boys, affiliated with the First Rusafa Baghdad Governorate Education Directorate. It amounted to (65) students in (2) two classes. Random selection fell on group (A), consisting of (32) students to represent the control group, and group (B), consisting of (33) students to represent the experimental group. The two groups were rewarded with the following variables (intelligence, chronological age, mental concentration scale). The mental focus scale tool consisted of five dimensions: (the tendency toward mastery, organization, intellectual clarity, attention, and a feeling of comfort when engaging in solving problems). Psychometric properties and reliability were calculated. The data was analyzed and processed statistically using the statistical package (SPSS)At the end of the experimeent ,the researcheer aplied the mental focus scaale tothe students of both groups. Their answers were corected and treated statistically. The results of the research showed that the students of the experimental group were superior to the students of the control group in mental focus. In light of the results that were reached, the researcher drew some conclusions and recommended some recommendations